2011
DOI: 10.1002/pts.947
|View full text |Cite
|
Sign up to set email alerts
|

Review of Package Warning Labels and Their Effect on Consumer Behaviour with Insights to Future Anticounterfeit Strategy of Label and Communication Systems

Abstract: This paper investigates and reviews literature regarding a range of topics important to the research questionthe themes apply across all the topics. The topics include label and package warnings, including tamperevident features, to review their effect on the consumer behaviour of changing usage or purchase decisions. This information was then applied to gain insight into anticounterfeit product/package efforts. Based on this research, it appears that there is value for brand marketers to enhance their anticou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 59 publications
(123 reference statements)
0
26
0
Order By: Relevance
“…Placement of warnings plays a crucial role, as it is intended to prevent mishaps such as injury or adverse drug events. 32 A majority of the participants in the current study worked in the health care field. A similar study conducted in college students showed results akin to our results.…”
Section: Discussionmentioning
confidence: 99%
“…Placement of warnings plays a crucial role, as it is intended to prevent mishaps such as injury or adverse drug events. 32 A majority of the participants in the current study worked in the health care field. A similar study conducted in college students showed results akin to our results.…”
Section: Discussionmentioning
confidence: 99%
“…While the FD&C Act is the tool used to address food fraud, there are other applicable regulations that cover such areas as intellectual property rights, fair labeling, tampering, theft, consumer product safety, and product importation (Spink and others 2011). The laws and regulations covering food fraud and consumer product counterfeiting are diverse because they were developed from regulatory or statutory responsibilities outward, specific to the known fraud types and the criminals—this inherent complexity creates both coverage gaps and overlaps that impede food fraud enforcement efforts.…”
Section: Laws Regulations and Standardsmentioning
confidence: 99%
“…Effective enforcement is a challenge because the food fraud risk is emerging, evolving and extremely complex. For example, the deliberate misidentification of packaged food potentially involves a variety of regulatory violations under the jurisdiction of various regulatory and enforcement agencies (Spink and others 2011). Food ingredient statements are the regulatory and statutory domain of the FDA.…”
Section: Laws Regulations and Standardsmentioning
confidence: 99%
“…In other words, the packaging can actually whet a person's appetite and cause a person to overeat, therefore leading to obesity. Spink et al (2011) examined whether consumers can assimilate and correctly understand the information on a product container. They pointed out, for example, that a warning of DANGER on the label may change consumer behavior and cause a person not to purchase the product.…”
Section: Introductionmentioning
confidence: 99%
“…They pointed out, for example, that a warning of DANGER on the label may change consumer behavior and cause a person not to purchase the product. They found that packaging influences buying decisions, may possibly lead to information being interpreted incorrectly, and could have an impact on sales (Spink et al, 2011). …”
Section: Introductionmentioning
confidence: 99%